Energy audit data for a resort island in the South China Sea - Basir Khan M.R.; Jidin R.; Pasupuleti J. (Elsevier Inc., 2023)
Energy conservation; Renewable energy resources; Audit data; Energy audit; Load profiles; Load type; Optimal combination; Renewable energies; Resort island; South China; South China sea; Tioman; Diesel fuels